Self-perceived burden and associated factors in Chinese adult epilepsy patients: A cross-sectional study - Tang, Binmi; Fu, Yaqian; Liu, Birong; Yi, Qifeng (Frontiers in Neurology, 2022)
Objectives: Epilepsy requires long-term or lifelong treatment, and patients are prone to financial, emotional and psychological burdens that can cause psychological changes during the treatment process. This study aimed to describe the prevalence and associated factors of Self-Perceived Burden (SPB) in Chinese adult epilepsy patients, informing the treatment and nursing of epilepsy. Methods: A total of 143 adult epilepsy patients were included in this study, and the clinical questionnaire survey was conducted at the Third Xiangya Hospital of Central South University in Hunan, China, from March 2022 to June 2022. The sociodemographic and clinical characteristics of adult epilepsy patients were collected using a self-developed questionnaire, and the data on SPB, stigma and quality of life were collected through the Self-Perceived Burden Scale (SPBS), Kilifi Stigma Scale for Epilepsy (KSSE) and Quality of Life in Epilepsy Inventory-31 (QOLIE-31). Multiple linear regression analysis was used to determine the associated factors influencing SPB in adult epilepsy patients. Results: The average score of SPBS for the 143 adult epilepsy patients was 30.77 (SD=9.064), and 89.5% of them had obvious SPB. The results of the univariate analysis showed that residence, monthly household income, duration of epilepsy, type of medication and electroencephalogram findings were associated with SPB (P < 0.05). In Spearman correlation analysis indicated that SPBS score were positively correlated with KSSE score (r = 0.510, P < 0.05) while negatively correlated with QOLIE-31 score (r = -0.506, P < 0.05). Multiple linear regression analysis revealed that factors such as KSSE, type of medication, residency, and electroencephalogram finding accounted for 32.8% of the factors influencing SPB in adult epilepsy patients. Conclusion: 89.5% of adult epilepsy patients have varying degrees of SPB, which is associated with high stigma and poor quality of life. Therefore, during the treatment and nursing of adult epilepsy patients, clinical staff should pay attention to the psychological status of patients, help them reduce their psychological burden, and guide them to develop a healthy lifestyle.